Fabry disease as a trigger of immune-mediated glomerular disease: Clinical hypotheses and literature review - Javier Martínez de Victoria Carazo; Haylen Marin; Francisco Javier De la Hera Fernández; Carlos Mañero Rodríguez; César Ramírez Tortosa; José Luís Callejas Rubio (Nefrología (English Edition))
Fabry disease (FD) is an X-linked genetic disorder characterized by alpha-galactosidase deficiency, leading to the accumulation of globotriaosylceramide. This accumulation causes multi-organ dysfunction, with renal involvement being particularly significant. Recently, the immunological relationship of this disease has been investigated, including the inactivation of enzyme therapies by antibodies and systemic inflammation. We present the case of a 15-year-old patient with FD and ANCA-associated vasculitis (AAV). A narrative review was conducted by searching PubMed with the terms “Fabry disease” AND “vasculitis” AND “glomerulonephritis,” identifying 9 relevant articles. These cases were compared with the current one, emphasizing pathophysiological aspects. 75% of patients had fever, 50% had peripheral edema, and 25% had otorhinolaryngological involvement. Pauci-immune necrosis was found in 75%. Therapeutically, all cases were treated with plasmapheresis, 75% with cyclophosphamide, and only one case required hemodialysis during follow-up. The association of FD with vasculitis is rare, with only five cases, only one with positive ANCA. The role of the immune system in FD, still not fully understood, seems to contribute significantly to pathogenesis and complications. This case highlights the need for further research on the immunological role in FD and its relationship with vasculitis and other autoimmune diseases. Resumen: La enfermedad de Fabry (EF) es un trastorno genético ligado al cromosoma X caracterizada por deficiencia de alfa-galactosidasa, que conduce a la acumulación de globotriaosilceramida. Dicha acumulación causa una disfunción multiorgánica, siendo particularmente significativo el compromiso renal. Recientemente, se ha investigado la relación inmunológica de esta enfermedad, incluyendo la inactivación de las terapias enzimáticas por parte de los anticuerpos y la inflamación sistémica. Presentamos el caso de un paciente de 15 años con EF y vasculitis asociada a ANCA (VAA). Se realizó una revisión narrativa mediante la búsqueda en PubMed de los términos «Fabry disease» Y «vasculitis» Y «glomerulonephritis», identificando 9 artículos relevantes. Dichos casos fueron comparados con el actual, destacando los aspectos patofisiológicos. El 75% de los pacientes tuvo fiebre, el 50% edema periférico y el 25% compromiso otorrinolaringológico. Se encontró necrosis pauciinmune en el 75% de los casos. Terapéuticamente, todos los casos fueron tratados con plasmaféresis, el 75% con ciclofosfamida, y solo un caso requirió hemodiálisis durante el seguimiento. La asociación de la EF con vasculitis es rara, encontrándose solo 5 casos, siendo únicamente uno positivo a ANCA. El rol del sistema inmunológico en la EF, que aún no se comprende plenamente, parece contribuir significativamente a su patogenia y complicaciones. Este caso destaca la necesidad de investigación futura sobre el rol inmunológico en la EF y su relación con vasculitis y otras enfermedades autoinmunes.